The association of cardiometabolic multimorbidity with depression and length of hospitalization: a population-based cross-sectional study among adults in Turkey - Ali Köse; Mehmet Emin Arayici; Hatice Simsek (BMC Public Health)
Abstract Background Recent developments suggest a strong association between cardiometabolic multimorbidity, depression, and hospitalization. The aim of this study was to investigate the association of cardiometabolic multimorbidity with depression and the length of hospitalization among individuals aged 40 and older. Methods This study is based on the secondary analysis of data obtained from the 2022 Turkey Health Survey conducted by the Turkish Statistical Institute (TUIK). A weighted sample of 31,425,252 individuals aged 40 and over was analyzed. The dependent variables of the study are depression and hospitalization, while the independent variable is cardiometabolic multimorbidity. Other covariates include gender, age, education level, physical activity, body mass index, tobacco use, and alcohol use. The weights from the database provided by TUIK were used in the data analysis. The relationship between cardiometabolic multimorbidity and depression was investigated using univariate and multivariate logistic regression analysis. Result Of the included participants, 51.2% were female and 35.5% were between the ages of 40–49. In Model 1, individuals with five cardiometabolic diseases had a 10-fold higher risk of developing depression compared to those with no diseases (OR: 10.0; 95% CI: 9.82–10.23). In Model 2, the risk of depression was 5.1 times higher in individuals with three diseases (OR: 5.1; 95% CI: 5.08–5.14), 5.83 times higher in those with four diseases (OR: 5.3; 95% CI: 5.78–5.88), and 14.6 times higher in individuals with five diseases (OR: 14.6; 95% CI: 14.36–14.99). Furthermore, as the number of cardiometabolic diseases increases, a significant increase in the length of hospitalization was observed (p < 0.001). Conclusions The findings of this study revealed that cardiometabolic multimorbidity may increase the risk of depression and the length of hospitalization in adults. These results may provide guidance for developing disease prevention and control strategies regarding cardiometabolic multimorbidity and associated factors in adults.